Adaptasi dan Validasi Online Vigilance Scale (OVS) Versi Bahasa Indonesia - Galuh Dianasti; Akhmad Ali Akbar; Hanif Akhtar (Buletin Riset Psikologi dan Kesehatan Mental, 2026)
The rapid development of digital technology has increased individuals’ connectedness to the online world, particularly among young people in Indonesia. This condition has given rise to the phenomenon of Online Vigilance, defined as the tendency to remain cognitively aware of, engaged with, and responsive to digital activities. The Online Vigilance Scale (OVS) is a primary instrument used to measure this phenomenon; however, an Indonesian version has not yet been available. This study aimed to adapt the OVS into Indonesian and to examine its validity and reliability within the Indonesian cultural context. The scale adaptation followed the standards and recommendations of the International Test Commission guidelines. The study involved 306 participants, predominantly aged 18-35. Participants were recruited using an accidental sampling technique. Reliability analysis indicated good internal consistency across all three OVS dimensions. The factor structure was tested using CFA and supported a three-dimensional model consistent with the original construct.